Super-strengths in elite sport - Ludlam, K. E. (Sheffield Hallam University, 2017)
The intention of this PhD was to develop a conceptual pathway for how a novel approach termed super-strengths can be delivered by Sport Psychology practitioners, and to investigate the effects of the approach. The rationale for exploring this particular strengths-based approach (super-strengths) was that although this way of working has scarcely featured in the sport psychology literature, strengths-based approaches have been reported to have positive effects on psychological characteristics and performance in various similar domains. The purpose of the first study of the thesis was to gain an insight into how super-strengths is being used in elite sport, and to develop an initial conceptual pathway for understanding and implementing the approach. The aims were three-fold: first, to explore the meaning of super-strengths; second to explore how super-strengths are identified; and finally to capture the key phases for implementing the approach. To do so, the study explored how sport psychologists (n=7) and coaches (n=8), had co-delivered a super-strengths approach with UK elite athletes. Findings from the semi-structured interviews were categorized into three general dimensions: defining super-strengths, identification methods, and phases of development. Super-strengths were defined as a strategy for performance, utilizing a potential world`s-best resource to gain a competitive edge in a performance context. Identification methods were subjective (e.g., asking/observing athletes) and objective (e.g., performance analysis). Participants emphasized three development phases: preparation, adaptation, and monitoring. The findings of the study reinforced the need to obtain athletes` perceptions of super-strengths to explore their experiences of the approach. Thus, the purpose of the second study was to gain understanding of athletes` perceptions of the role and effects of engaging with super-strengths, in relation to their psychological characteristics and performance in elite sport. Semi-structured interviews were conducted with athletes (n=12) who had previous experience of working with a sport psychology practitioner on super-strengths. Thematic analysis of the data (Braun & Clarke, 2006) indicated that super-strengths had a positive influence on athletes` mind-set, confidence, clarity of purpose, drive, coping ability, and performance. Findings highlighted the potential benefits of adopting strengths-based approaches in sport, and together with the findings from study one suggested that sport psychology (SP) practitioners conducting a super-strengths intervention with elite athletes could potentially facilitate both psychological and performance gains. Thus the next investigation comprised a two-phased super-strengths intervention in an elite sport setting. The aims of phase one were twofold: to preliminarily investigate the practicality of a) delivering a super-strengths intervention guided by the conceptual pathway generated from studies one and two; and b) employing sport-specific self-report measures as a way of evaluating efficacy, guided by the findings of study two. The intervention was conducted with amateur boxers. Measures employed were informed by the findings of study two, and therefore assessed athletes` confidence, engagement, basic needs satisfaction, coping skills, and performance. Findings suggested that the intervention was well received by athletes and there were evident positive changes detected from the psychometric measures. Building on these findings, phase two of the intervention research involved a more in-depth, refined super-strengths intervention whereby a single subject, multiple baseline design was employed with athletes (n=3) from different elite sport settings (cricket, shooting, football). The findings indicated the efficacy of a super-strengths intervention for facilitating positive changes in confidence, engagement, needs satisfaction, coping, and performance in elite sport. In conclusion, this thesis has enabled an in-depth understanding to be gained on the role of super-strengths, how it can be delivered in elite sport settings, and the potential benefits it can have on athletes` psychological factors and performance